Mitochondrial metabolism determines the functional status of human sperm and correlates with semen parameters - Irigoyen, Pilar; Pintos-Polasky, Paula; Rosa-Villagran, Lucia; Skowronek, Maria Fernanda; Cassina, Adriana; Sapiro, Rossana (Frontiers in Cell and Developmental Biology, 2022)
The diagnosis of male infertility is based essentially on the patient's medical history and a standard semen analysis. However, the latter rarely provides information on the causes of a possible infertility, emphasizing the need to extend the analysis of the sperm function. Mitochondrial function has been associated with sperm function and dysfunction, the latter primarily through the production of excessive amounts of reactive oxygen species (ROS). We hypothesized that analysis of sperm mitochondrial metabolism together with sperm ROS production could be an additional tool to improve routine semen analysis, after appropriate validations. To test our hypothesis, we performed several experiments using a non-routine method (high-resolution respirometry, HRR) to access mitochondrial function. First, we investigated whether mitochondrial function is related to human sperm motility and morphology. When mitochondrial metabolism was challenged, sperm motility decreased significantly. Additionally, morphological abnormalities in the sperm mid-piece and mitochondria were associated with global sperm defects evaluated by routine methods. Subsequently, sperm mitochondrial function was assessed by HRR. Respiratory control ratio (RCR) was determined and evaluated in the context of classical sperm analysis. In parallel, sperm hydrogen peroxide (H2O2) production and seminal plasma (SP) antioxidant capacity were measured. The percentage of sperm with progressive motility correlated positively with RCR, SP antioxidant capacity, and negatively with the concentration of extracellular H2O2 production ([H2O2]). The percentage of normal sperm morphology correlated positively with RCR and negatively with [H2O2]. Sperm morphology did not correlate with seminal plasma antioxidant capacity. Furthermore, Receiver Operating Characteristic curves were used for the first time to test the diagnostic ability of RCR, [H2O2], and SP antioxidant capacity as binary classifiers. An RCR cut off value of 3.2 was established with a sensitivity of 73% and a specificity of 61%, using reference values considered normal or abnormal in routine semen analysis. The cut off value for [H2O2] was 0.2μM/106 sperm (sensitivity=65%, specificity=60%). There were no reference values for SP antioxidant capacity that distinguished between abnormal and normal sperm samples. We conclude that sperm mitochondrial function indices in combination with [H2O2] may be useful tools to complement the routine semen analysis.